The Future of Energy Networks in a Decarbonized World - Rahmat Poudineh (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2022)
This issue of the Oxford Energy Forum (OEF) is dedicated to the future of energy networks in a decarbonised world. The net-zero carbon target will result in a significant change in energy systems with important implications for existing energy networks. Electricity networks are going to bear the brunt of energy sector transformation because of their role in the decarbonization of the transport, building and industrial sectors. The increased variability of supply and demand along with penetration of distributed energy resources can create new constraints in electricity networks and thus necessitate more efficient utilization of existing grid assets, new grid investments, and in some cases even new overall grid and electricity market designs. The future of natural gas networks, however, is highly uncertain especially at the low-pressure distribution level. An idea is to repurpose existing gas infrastructures to transport hydrogen but that is not straightforward. There are other energy networks such as district heating and cooling which although currently they have a little energy demand market share globally, their share is expected to increase because of their advantage over individual heating/cooling systems in high-density built environments. These all mean that it is necessary to understand how best to design, regulate, integrate and operate existing and emerging energy networks in order to lower the costs and challenges of achieving decarbonisation targets.
Keywords: 330